2019
DOI: 10.1016/j.jeurceramsoc.2019.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Effects of quenching on phase transformations and ferroelectric properties of 0.35BCZT-0.65KBT ceramics

Abstract: Solid solutions of 0.35(Ba,Ca)(Zr,Ti)O3-0.65(K0.5Bi0.5)TiO3 (BCZT-KBT) having various Ca and Zr contents were synthesized by solid state reaction. The sintered ceramics exhibited interesting features comprising core-shell type microstructures and relaxor ferroelectric behaviour. The influence of air-quenching on structure and electrical properties has been systematically investigated. The results indicate that the compositional heterogeneity in the shell regions, for the slow-cooled state, was reduced by air q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 48 publications
2
6
0
Order By: Relevance
“…This then entails an increased correlation between the existing PNRs apart from providing means of tailoring ergodicity as an alternative to new solid solutions or chemical doping. A similar increase in the correlation length of PNRs was facilitated in ergodic relaxor (Ba, Ca)(Ti, Zr)O 3 ‐K 1/2 Bi 1/2 TiO 3 by quenching; although driven by chemical heterogeneity (unlike the present study), the quenched samples exhibited enhanced non‐cubic (tetragonal) phase fraction as opposed to the slow‐cooled specimens 41 …”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…This then entails an increased correlation between the existing PNRs apart from providing means of tailoring ergodicity as an alternative to new solid solutions or chemical doping. A similar increase in the correlation length of PNRs was facilitated in ergodic relaxor (Ba, Ca)(Ti, Zr)O 3 ‐K 1/2 Bi 1/2 TiO 3 by quenching; although driven by chemical heterogeneity (unlike the present study), the quenched samples exhibited enhanced non‐cubic (tetragonal) phase fraction as opposed to the slow‐cooled specimens 41 …”
Section: Resultssupporting
confidence: 64%
“…A similar increase in the correlation length of PNRs was facilitated in ergodic relaxor (Ba, Ca)(Ti, Zr)O 3 -K 1/2 Bi 1/2 TiO 3 by quenching; although driven by chemical heterogeneity (unlike the present study), the quenched samples exhibited enhanced non-cubic (tetragonal) phase fraction as opposed to the slowcooled specimens. 41 In NBT-6BT, it has been demonstrated that Bi-O and Bi-Ti bond distances feature an abrupt change at T m but not at T F-R , indicating the transformation from rhombohedral to tetragonal phase to occur gradually. However, a recent report indicated that quenching results in enhanced Bi 3+ offcentering as opposed to furnace-cooled specimens, 32 which can alter the local structure.…”
Section: Resultsmentioning
confidence: 99%
“…This is because that the polarization are nonsaturated at 6 kV/mm, and appropriate high temperature can promote the movement of domain walls and thus favor the polarization reversal. 38,39 However, with further increase in temperature, the depolarization behavior becomes dominant and the long-range FE order diminishes into polar nano regions (PNRs), reducing the polarization. 32 In addition, the temperature at which the maximum P r appears increases with the increase in T s , which is 90°C, 100°C, and 120°C for the samples sintered at T s = 1100°C, 1140°C, and 1180°C, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In another lead‐free family, the Na 0.5 Bi 0.5 TiO 3 ‐based piezoceramics, quenching from the sintering temperature was used to defer the ferroelectric‐relaxor transition temperature ( T F‐R ) to higher values, thereby improving the thermal stability of ferro/piezoelectric properties . In the solid solutions of 0.35(Ba,Ca)(Zr,Ti)O 3 –0.65(K 0.5 Bi 0.5 )TiO 3 , the quenching process was again used to enhance polarization and increase thermal stability of the ceramics …”
Section: Introductionmentioning
confidence: 99%
“…14,15 In the solid solutions of 0.35(Ba,Ca)(Zr,Ti)O 3 -0.65(K 0.5 Bi 0.5 ) TiO 3 , the quenching process was again used to enhance polarization and increase thermal stability of the ceramics. 16 In the current study, Pb(Mg 1/3 Nb 2/3 )O 3 -PbZrO 3 -PbTiO 3 (PMN-PZT) ternary system was chosen and investigated to improve the soft piezoelectric properties through a compositional variation and development of crystallographic texture, as an initial focus. PMN is a relaxor ferroelectric with high dielectric properties at room temperature, whereas PZT is a normal ferroelectric with higher piezoelectric and ferroelectric properties.…”
Section: Introductionmentioning
confidence: 99%